Limited attention and choice - Karen Kaiser (Banco de México, 2010)
This paper analyzes a boundedly rational decision maker who is uncertain about his preference and faces the following trade-off: adding a good to the choice set has a positive option value but increases the complexity of the choice problem. The increased complexity is modeled as a reduction of the information available for each good. Because of this trade-off there is an optimal number of goods that the decision maker wants to analyze before making his final choice. The choice of the optimal set can be interpreted as the choice among stores. Stores maximize profits and choose a quality, an assortment, and a price. A lower cost of providing quality implies higher price and higher quality. Assortment will be small for very high levels of quality. Better quality of information implies greater variety and higher price. Greater variety combined with good consumer service can be a signal for high quality of the store.
Keywords: D01; D11; D21; 330; Decision making; Bounded rationality; Choice set; Stores; Quality